Three-quarter DMEK in eyes with glaucoma draining devices to avoid secondary graft failure - Oganesyan, Oganes; Makarov, Pavel; Grdikanyan, Arthur; Oganesyan, Carolina; Getadaryan, Vostan; Melles, Gerrit R J (Acta ophthalmologica, 2021)
PURPOSE: To present a case series of a modified three-quarter Descemet's membrane endothelial keratoplasty (3/4-DMEK) technique to treat pseudophakic bullous keratopathy in the presence of a glaucoma drainage device (GDD) tube in the anterior chamber by reducing the risk of donor endothelial damage due to absence of donor endothelial cells overlying the GGD tube area. METHODS: In this prospective case series, four eyes of three patients with stable glaucoma underwent 3/4-DMEK surgery for pseudophakic bullous keratopathy after GDD insertion. The patients were followed up to 24 ± 2.5 months postoperatively. RESULTS: No intraoperative or postoperative complications were noted. The average central endothelial cell density (ECD) was 1093 ± 74 cells/mm2 at 12 months postoperatively, corresponding to an ECD decrease of 58 (±6)% as compared to preoperative values. Average best-corrected visual acuity increased from finger counting before surgery to 20/60 (logMar 0.5) at 12 months after 3/4-DMEK and remained stable up to 24 months postoperatively. All corneas remained clear at the last available follow-up. CONCLUSION: This case series demonstrates the technical feasibility of 3/4-DMEK in eyes with pseudophakic bullous keratopathy in the presence of a GDD tube. The absence of a donor DM and donor cells above the silicone tube excludes direct tube contact with the graft. Longer term studies are needed to show the effect of this modified graft pattern and dimensions on transplant survival.
Keywords: senioři; rejekce štěpu; Prosthesis Design; glaukom; přežívání štěpu; senioři nad 80 let; Pseudophakia; Time Factors; mužské pohlaví; Graft Survival; rohovkový endotel; Descemet Stripping Endothelial Keratoplasty; Prospective Studies; Glaucoma; pseudofakie; Follow-Up Studies; endothelial failure; protézy - design; následné studie; Aged, 80 and over; Glaucoma Drainage Implants; ženské pohlaví; Graft Rejection; Humans; prospektivní studie; zraková ostrost; drenážní implantáty glaukomové; Visual Acuity; Descemet’s membrane endothelial keratoplasty; časové faktory; zadní lamelární keratoplastika; Endothelium, Corneal; refrakce oka; 3/4-DMEK; corneal transplantation; quarter Descemet’s membrane endothelial keratoplasty; Female; Aged; Refraction, Ocular; lidé; Male